First Genomic Analysis of Dendritic Cells from Lung and Draining Lymph Nodes in Murine Asthma. (24th February 2015) - Tschernig, Thomas; Hartwig, Christina; Jeron, Andreas; Dinh, Quoc Thai; Gereke, Marcus; Bruder, Dunja
Abstract : Asthma is the consequence of allergic inflammation in the lung compartments and lung-draining lymph nodes. Dendritic cells initiate and promote T cell response and drive it to immunity or allergy. However, their modes of action during asthma are poorly understood. In this study, an allergic inflammation with ovalbumin was induced in 38 mice versus 42 control animals. After ovalbumin aerosol challenge, conventional dendritic cells (CD11c/MHCII/CD8) were isolated from the lungs and the draining lymph nodes by means of magnetic cell sorting followed by fluorescence-activated cell sorting. A comparative transcriptional analysis was performed using gene arrays. In general, many transcripts are up- and downregulated in the CD8 − dendritic cells of the allergic inflamed lung tissue, whereas few genes are regulated in CD8 + dendritic cells. The dendritic cells of the lymph nodes also showed minor transcriptional changes. The data support the relevance of the CD8 − conventional dendritic cells but do not exclude distinct functions of the small population of CD8 + dendritic cells, such as cross presentation of external antigen. So far, this is the first approach performing gene arrays in dendritic cells obtained from lung tissue and lung-draining lymph nodes of asthmatic-like mice.